Legal Anthropology of Pluralism and the Commercialized Public Sphere in Tourism : Antropologi Hukum dari Pluralisme dan Ruang Publik yang dikomersialkan dalam Pariwisata - Dewa Gede Edi Praditha; I Gusti Ayu Sita Maharani (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Bali tourism is globally recognized for its strong integration of cultural values and spirituality rooted in the Tri Hita Karana philosophy, emphasizing harmony among humans, nature, and the divine. Specific Background: This philosophy has been formally institutionalized through Bali Provincial Regulation No. 5 of 2020, which mandates culturally based tourism governance. Knowledge Gap: Despite its normative adoption, the practical implementation of Tri Hita Karana within tourism development and public space management remains inconsistent and insufficiently examined from a socio-legal perspective. Aims: This study aims to analyze the application of Tri Hita Karana values and explore the dynamics of legal pluralism and law enforcement in Bali’s tourism sector. Results: The findings reveal that although Tri Hita Karana is embedded in regional policy, its implementation is constrained by weak supervision, dominance of economic interests, environmental degradation, commercialization of public and sacred spaces, and limited cultural awareness among tourists. Additionally, the interaction between state law, customary law, and socio-religious norms creates complex legal pluralism, where enforcement is often inconsistent and influenced by power relations and economic pressures. Novelty: This study provides a socio-legal analysis linking Tri Hita Karana marginalization with legal pluralism and power dynamics in tourism governance. Implications: Strengthening regulatory enforcement, enhancing institutional synergy, and reinforcing cultural awareness are essential to ensure balanced tourism development aligned with cultural preservation and environmental sustainability in Bali. Highlights: Cultural philosophy is formally recognized but inconsistently applied in tourism practices. Economic priorities and investment pressures dominate spatial and regulatory decisions. Interactions between state, customary, and socio-religious norms shape uneven law enforcement. Keywords: Tri Hita Karana, Legal Pluralism, Bali Tourism, Cultural Governance, Public Space Commercialization